2016
DOI: 10.1186/s12875-016-0456-5
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional collaboration regarding patients’ care plans in primary care: a focus group study into influential factors

Abstract: BackgroundThe number of people with multiple chronic conditions demanding primary care services is increasing. To deal with the complex health care demands of these people, professionals from different disciplines collaborate. This study aims to explore influential factors regarding interprofessional collaboration related to care plan development in primary care.MethodsA qualitative study, including four semi-structured focus group interviews (n = 4). In total, a heterogeneous group of experts (n = 16) and hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
112
1
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(130 citation statements)
references
References 25 publications
10
112
1
7
Order By: Relevance
“…It is important that although it is a collaborative environment, individual team members still feel supported and recognized in their professional role (Regan et al, 2016). Working collaboratively requires time to engage with others, so adequate staffing is also important to relieve time constraints for professionals and administrative support can help with documentation and organizational tasks (van Dongen et al, 2016;Orchard et al, 2005;Regan et al, 2016). Orientation programs should be provided to introduce professionals to the different disciplines within the healthcare team, encouraging them to share their roles, responsibilities, skills, and knowledge (Orchard, 2010;Reese & Sontag, 2001).…”
Section: Fundamentals Of Interprofessional Educational and Collaboratmentioning
confidence: 99%
See 4 more Smart Citations
“…It is important that although it is a collaborative environment, individual team members still feel supported and recognized in their professional role (Regan et al, 2016). Working collaboratively requires time to engage with others, so adequate staffing is also important to relieve time constraints for professionals and administrative support can help with documentation and organizational tasks (van Dongen et al, 2016;Orchard et al, 2005;Regan et al, 2016). Orientation programs should be provided to introduce professionals to the different disciplines within the healthcare team, encouraging them to share their roles, responsibilities, skills, and knowledge (Orchard, 2010;Reese & Sontag, 2001).…”
Section: Fundamentals Of Interprofessional Educational and Collaboratmentioning
confidence: 99%
“…This may also include the preparation, structuring, and organization of regular interprofessional team meetings, promoting and guiding reflection and discussion (van Dongen et al, 2016). Hepp et al (2015) found that currently many interprofessional collaborative practice experiences are burdened with weaknesses in this area, stating collaborative leadership as an essential component to foster collaborative partnerships.…”
Section: Fundamentals Of Interprofessional Educational and Collaboratmentioning
confidence: 99%
See 3 more Smart Citations